Assessment of Sustainable Economic Development: Where We Are Today - Sarma Aralas (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
The three pillars of sustainability address the social, economic, and environmental aspects of development. This paper discusses sustainable economic development assessment of countries using data by country and region, with an emphasis on the Asian and Southeast Asian areas. Sustainable economic development assessment may provide a measure of a country’s sustainable economic growth as well as its citizen’s well-being based on three development categories, namely, economics, investments and sustainability. The three categories are comprised of ten dimensions which include income, economic stability, education, infrastructure, and equity. The objective of this paper is to attempt to identify priority areas for sustainable development that align with economic and social goals, in particular for Malaysia. Through the processes of benchmarking and identification of sustainable development aspects, a ranking of sustainable economic development assessments may shed light on how countries may move towards the achievement of sustainable development goals.